Kesiapan Satgas Desa Tangguh Bencana Dalam Menghadapi Bencana Di Kecamatan Tanjungkerta - Rifdah Nur Fadlilah; Hikmat Pramajati; Imam Tri Sutrisno (Universitas Negeri Gorontalo, 2025)
Tanjungkerta District is an area with a relatively high level of disaster risk, which requires strong preparedness from the community, particularly through the role of the Disaster-Resilient Village Task Force. This study aims to describe the preparedness level of task force members in carrying out disaster management efforts. The research employed a descriptive quantitative design with a total of eighty-five respondents selected through total sampling. Data were collected using a questionnaire assessing four aspects of preparedness, namely training experience, readiness for assignment, access to information, and governance and institutional support. The findings show that training experience obtained an average score of 3.46 and readiness for assignment reached 3.61, both categorized as ready. Governance and institutional support also fell into the ready category with an average score of 3.57. Meanwhile, access to information received an average score of 3.20, indicating an almost ready level. Overall, the preparedness level of the task force was categorized as ready with an average score of 3.43. These results indicate that the task force has demonstrated good preparedness; however, further strengthening of information access and continuous capacity development is still required.